Analysis of King Cobia Fish Commodity Value Chain as an Effort to Increase the Value of Frozen Fish Products - Leni Herdiani; Neni Sumarni; Enjang Suherman; Suroso Suroso (Almana : Jurnal Manajemen dan Bisnis, 2023)
King Kobia is a rising marine fish commodity and continues to be socialized by cultivators in Pangandaran. Weaknesses of fishery products include the fast decay process, so to prevent this process, proper handling techniques are needed so that the freshness and quality of the fish are guaranteed. This study aimed to map the flow of king cobia products, analyze the king cobia value chain, analyze the added value, and describe the obstacles that exist in the processing and marketing of product value. The type of research used is descriptive research. Descriptive research aims to describe something by describing, recording, analyzing, and interpreting the conditions in a value chain of king cobia fish commodities. Data collection through literature study, observation, documentation, and interviews with fishermen, MSME actors, and fish traders. Data analysis using Value Chain Analysis. The study found that value chain analysis helps add value in every production stage and delivery of products or services to consumers. This value chain consists of two parts, primary activities, and supporting activities. In contrast, the added value analysis is fish nuggets as an effort to increase the value of frozen fish products.